"Meaning" in Social Media. (29th April 2015) - Lomborg, Stine
Researchers of social media struggle to stay up to speed: empirical findings are most often very context- and time-specific and quickly become outdated because the object of study changes. By extension, previously solid and well-tested methods and tools may be rendered obsolete, for instance, as social media services change their application programming interfaces (APIs). The stabilizing component in social media research is arguably good theory—about the communicative patterns and bit trails of use, the actions that social media channel and mobilize, the interplay between social and other media, and, of course, the implications of social media for sociality, privacy, and society at large. In this essay, the concept and study of meaning is proposed as a key concern for social media research. "Meaning" highlights the generative process by which users negotiate the communicative potentials and constraints of a text or a medium vis-a-vis the individuals' preexisting mental models, expectations, and intentions in context.